Effects of vitamin E supplementation on blood antioxidants levels in patients with Behcet's disease - Kökçam, I; Naziroglu, M (Pergamon-Elsevier Science Ltd, 2002)
Behqet's disease (BD) is known for many years, yet its etiology remains unknown. In BD, the increased production of reactive oxygen species from activated neutrophils may reduce concentrations of antioxidant vitamins and enzymes in plasma and red blood cells (R-BC). Vitamin E is an important fat soluble antioxidant and its role on antioxidant parameters of BD is unclear. The study was undertaken to evaluate the role of vitamin E on lipid peroxidation (MDA) levels, antioxidant vitamin and enzyme concentrations in plasma and RBC in patients with BD. There were three groups i.e., control, patient and treatment groups with twenty-five subjects in each. Nonsmoking patients with BD, patient group, was compared with an equal number of healthy control subjects (control group). Blood samples were taken from both control and patient groups and then oral vitamin E was daily supplemented to the patients with BD for six weeks (treated group). At the end of six weeks, blood was taken from the treated group once more. RBC and plasma MDA levels, serum neopterin, complement system (C-3 and C-4), ASO, CRP, rheumatoid factor, plasma lipoprotein (a), total cholesterol concentrations and erythrocyte sedimentation rate Were higher in the patient group than in the control group, but they were lower in the treatment group than in the patient group. While vitamins A, E and beta-carotene concentrations in plasma, catalase, glutathione peroxidase activities and reduced glutathione levels in RBC and plasma were lower in patient group than in the controls, they were found to be higher in the treatment group than in-the patient group. These results provide some evidence for a potential role of increased lipid peroxidation and decreased enzymatic and non enzymatic antioxidants in BD by its inflammatory character and vitamin E which may strengthen the antioxidant defense system, and may contribute to the treatment of BD. (C) 2002 The Canadian Society of Clinical Chemists. All rights reserved.
Keywords: oxidative stress; Behcet's disease; antioxidants; lipid peroxidation; vitamin E; inflammation